Relationships between Work Environment and Employee Engagement mediate by Job Satisfaction - Kemal H Simanjuntak; Usep Suhud; Dewi Susita (IJHCM (International Journal of Human Capital Management), 2023)
This research examines impact of work environment on employee engagement, and more that the role of job satisfaction as a mediator. We are empirically test relations between work environment and employee engagement mediate by job satisfaction in a national private bank in Indonesia. The data from questionnaires on job satisfaction, work environment and employee engagement collected from s survey that we received from 893 respondent via online. The structural model is based on four construct, which tested using structural equation modelling (SEM) using IBM SPSS v25 and IBM AMOS v24. An increase in work environment both positively relates to job satisfaction and employee engagement, and it shows also that job satisfaction mediate positively significant work environment to employee engagement. This research confirm that job satisfaction mediate work environment to employee engagement although it is never consluce yet from prom previous research. Work environment and job satisfactin both positively and significaly impact employee engagement and these constructs may strengthen employee engagement, as well as work environment impact to strengthen job satisfaction